Narrative deconstruction of gender discourses within relationships - Erasmus, Espagh (North-West University, 2004)
The purpose of this study is to weigh the potential inherent in a postmodernist, narrative approach to relationships. The discourse of the same orphan equality is deconstructed and an alternative discourse of differences is suggested. In this study, the discourse of the same orphan equality is deconstructed and used both positions, not to disqualify this discourse but to suggest an alternative narnlik the discourse of being different. In in this connection the metaphor "tandem cycling" is used to describe the nature of the suggest current discourse of relationships. This discourse suggests that relationships such as tandem cycling may be: it may be a wonderful ride through life. There are mountains, downhills, uphills, winds from front and back, sunsets and wild flowers to enjoy. It's easier times, there are hard times. In this study, the author attempts to represent the discourse of being different as alternative in relationships using a study from the brain to the socialization process and various communication methods. It was also used made from John Gray's case studies in his video to find differences between individuals emphasize and highlight the potential and creativity that goes with it let step. This confirms the possibilities that exist if the discourse of differences as an alternative to the discourse of the same orphan equality. It has gives the author the opportunity to explore new possibilities within relationships focus. The study also highlighted a variety of research possibilities which creates new opportunities for other researchers to discover. The cultural embedding discourses is a rich source of information that can make relationships creative influence. The biological differences emphasize that each individual is unique and therefore brings a myriad of potential with him to the relationship. It would bring new opportunities to look at relationships with new eyes. With this, the author wants to conclude and hopes that the study could make a small contribution to relationships can be seen in a new light.
Thesis (M.A. (Sociology))--North-West University, Vaal Triangle Campus, 2005.